(untitled) (BIRDEM Medical Journal, 2017)
Human life is intricately related to its surrounding environment which also harbors other animals and some deadly infectious pathogens. Any threat to the environment can thus increase the threat of new and so-called emerging infectious diseases (EIDs) especially novel viral infections called emerging viral diseases. This occurs partly due to changing climate as well as human interference with nature and animal life. An important event in new disease emergence is genetic changes in the pathogen that make it possible to become established in a new host species, productively infect new individuals in the new hosts (typically humans) and create local, regional or worldwide health threats. The world has witnessed some emerging and deadly viral threats in recent past with huge mortality and morbidity. Among them were severe acute respiratory syndrome (SARS), bird flu, swine flu, Middle East respiratory syndrome (MERS), ebola virus disease. Moreover some disease has caused great concern in certain regions including Bangladesh in terms of morbidity, like Nipah virus, Zika virus, Dengue and Chikungunya fever. Here in this article an attempt was made to briefly describe some of these emerging viral infections. Birdem Med J 2017; 7(3): 224-232